2021
DOI: 10.1097/iae.0000000000003055
|View full text |Cite
|
Sign up to set email alerts
|

LONGITUDINAL FLUORESCENCE LIFETIME IMAGING OPHTHALMOSCOPY ANALYSIS IN PATIENTS WITH MACULAR TELANGIECTASIA TYPE 2 (MacTel)

Abstract: Purpose: Fluorescence lifetime imaging ophthalmoscopy (FLIO) shows characteristic patterns in macular telangiectasia Type 2 (MacTel). This study investigates FLIO changes over time to better understand disease progression.Methods: Thirty-three patients with MacTel (age 60 ± 15 years) were followed at the Moran Eye Center with a prototype Heidelberg Engineering FLIO. The mean follow-up time was 19 ± 8 months (range 6-34 months). Fundus autofluorescence was excited at 473 nm, and FLIO lifetimes were recorded in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Figure 2 shows boxplots from ROIs. Similarly, comparing MacTelandDM with (7) and without (79) DR did not show any significant differences in ROIs (P values 0.589-1.0). Details are summarized in Table 3, summarizing Bonferroni-corrected P values (P values were not significant prior to correction).…”
Section: Fluorescence Lifetimes and Diabetes Statusmentioning
confidence: 78%
See 3 more Smart Citations
“…Figure 2 shows boxplots from ROIs. Similarly, comparing MacTelandDM with (7) and without (79) DR did not show any significant differences in ROIs (P values 0.589-1.0). Details are summarized in Table 3, summarizing Bonferroni-corrected P values (P values were not significant prior to correction).…”
Section: Fluorescence Lifetimes and Diabetes Statusmentioning
confidence: 78%
“…This prolongation occurs independently of changes in macular pigment. 7,14,15 As FLIO gives an en face image of retinal FLTs, it is difficult to attribute individual signals to specific structures at the posterior pole. A previous study focusing on retinal anatomy showed that the prolongation of FLTs in MacTel is influenced by ellipsoid zone loss.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…conducted a longitudinal study of FLIO in persons with MacTel and found that autofluorescence lifetimes slowly prolonged over time with very specific patterns. 34 Although such data on this condition may be informative in future developments of the MacTel classification, it will depend on how FLIO will be incorporated into clinical care. Currently, it is highly experimental and is limited by the small number of instruments available for testing.…”
Section: Discussionmentioning
confidence: 99%